NMR Methods for Characterization of Synthetic and Natural Polymers 2019
DOI: 10.1039/9781788016483-00299
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Molecular Dynamics of Semicrystalline Polymers as Studied by Solid-state NMR

Abstract: Chain-level structure of semicrystalline polymers in melt- and solution-grown crystals has been debated over the past several decades. Recently, 13C–13C double quantum (DQ) NMR spectroscopy and spin-dynamics simulation have been applied to trace chain trajectory and packing structure of 13C labeled polymers in melt- and solution-grown crystals. We highlight recent NMR studies for (i) packing structure, (ii) chain trajectory, (iii) conformation of the folded chains, (iv) nucleation mechanisms in the early stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 87 publications
0
8
0
Order By: Relevance
“…Herein, the obtained STD spectrum here could provide signals of ligands binding to QD suspended in aqueous solution. , The 1 H NMR spectrum of GG was shown in Figure c with the signal assignments assisted with the 1 H– 1 H homonuclear correlation spectrum (COSY, Figure S13). Figure d and Figure e show the STD spectra of GG-QD and peptide GG alone, respectively.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Herein, the obtained STD spectrum here could provide signals of ligands binding to QD suspended in aqueous solution. , The 1 H NMR spectrum of GG was shown in Figure c with the signal assignments assisted with the 1 H– 1 H homonuclear correlation spectrum (COSY, Figure S13). Figure d and Figure e show the STD spectra of GG-QD and peptide GG alone, respectively.…”
Section: Results and Discussionmentioning
confidence: 99%
“…When bulk water is selectively irradiated, the saturation of water protons will transfer to the ligands bounded to nanoparticles via spin diffusion, while the saturation transfer will not occur for the free ligands. As a result, the difference spectrum ( S off – S on ) will show the signal of the ligand interacting with the nanoparticles. , …”
Section: Results and Discussionmentioning
confidence: 99%
“…It should be noted that the recent advancements in ultrahigh magnetic field (above 1 GHz) and MAS probe technology (above 100 kHz spinning) have rendered proton-detected solid-state NMR methods the choice for structural analysis. By utilizing 2D 1 H-detected HETCOR experiments at 100 kHz MAS and 1.2 GHz (i.e., 28.2 T) magnetic field, Wiegand et al were able to capture the signals of an isolated trapped water molecule in a calix [4]arene lanthanide complex. 134 Brown et al further demonstrated the 1 H spectral resolution enhancement of 1 GHz compared to 600 MHz magnetic field, enabling insights into the specific hydrogen bonding interactions driving the crystal packing of Lorlatinib, an oral active pharmaceutical ingredient for treating lung cancer.…”
Section: Scanmentioning
confidence: 99%
“…1 Solidstate nuclear magnetic resonance (ssNMR) represents one of the most powerful approaches to address this challenge due to the presence of versatile time-and space-dependent NMR spin probes, namely spin interactions, such as chemical shift anisotropy (CSA), homonuclear/heteronuclear dipolar couplings, quadrupolar interactions, and so on. 2,3 The appropriate choice and ingenious manipulation of various spin interactions enable quantitative determination of structures on a length scale from angstroms to a few hundred nanometers and dynamics on a time scale from picoseconds to tens of seconds. 4−8 Specifically, ssNMR spectroscopy offers several unique advantages that are particularly well-suited for the study of structures and molecular dynamics of polymers.…”
Section: Introductionmentioning
confidence: 99%